2004
DOI: 10.1097/01.ju.0000104849.25168.6d
|View full text |Cite
|
Sign up to set email alerts
|

Residency Training in Percutaneous Renal Access: Does It Affect Urological Practice?

Abstract: This study suggests a relationship between training in percutaneous renal access and subsequent use of percutaneous renal procedures in the urologist's practice. Emphasis should be placed on providing continuing education opportunities to maintain competency in this important technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 6 publications
1
25
2
2
Order By: Relevance
“…This increasing role of flexible ureteroscopy has highlighted the training issues, because this procedure has a long learning curve and this learning process may increase the morbidity and cost of the surgery. For this reason, several training models have so far been developed to reduce the learning process of endourologic procedures [9,10,11,12,13,14]. However, all these reports have been published for percutaneous renal surgery training and to date no report has been published in the literature describing a model to aid urologists in RIRS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This increasing role of flexible ureteroscopy has highlighted the training issues, because this procedure has a long learning curve and this learning process may increase the morbidity and cost of the surgery. For this reason, several training models have so far been developed to reduce the learning process of endourologic procedures [9,10,11,12,13,14]. However, all these reports have been published for percutaneous renal surgery training and to date no report has been published in the literature describing a model to aid urologists in RIRS.…”
Section: Discussionmentioning
confidence: 94%
“…In the medical literature, several training models have been evaluated to date, consisting of different technical simulators and ex vivo or in vivo biological materials [9,10,11,12,13,14]. They concluded that an ideal training model needs to be realistic, commonly available and cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…A perceived lack of skill is also among the most common reasons given by urologists for not achieving percutaneous renal access. 11 Implicit in this self-assessed lack of skill is the difficulty inherent in translating the 2-dimensional images of intraoperative fluoroscopy into the 3D anatomy of the renal collecting system. This challenging portion of the procedure is hindered by 1 He depicted the anterior calyces as medial and the posterior calyces as lateral.…”
Section: Discussionmentioning
confidence: 99%
“…Cuando se realiza un entrenamiento formal en accesos percutáneos es más probable que después del entrenamiento, el médico proponga la nefrolitotricia percutánea como una opción a sus pacientes (27 vs Entrenamiento inanimado para acceso renal percutáneo 3 no la proponen argumentan que es un procedimiento que requiere mucha destreza en el acceso 31 . Existen pocos modelos para acceso renal percutáneo guiado y generalmente son biológicos, que requieren entrenamiento mediante repeticiones en riñones de cerdo 27,32,33 y exposición durante estas repeticiones a una dosis acumulada importante de radiación.…”
Section: Antecedentesunclassified